Implementation of the iSharing Application for Supervision of the Samapta Sat Patrol Unit in the Prevention of Theft in the Jurisdiction of the Kediri City Police - Wicaksono, Andhar (Indonesian Journal of Police Studies, 2024)
This research aims to describe the implementation of Samapta patrol supervision through the iSharing application in preventing criminal acts of motorbike theft in the jurisdiction of the Kediri City Police and describe the factors that influence the implementation of Samapta patrol supervision through the iSharing application in preventing criminal acts of motorbike theft in the jurisdiction of the Police. Kediri City. The method used in this research is a qualitative method. The data that has been collected was obtained by conducting direct interviews. Based on the findings of this research, it was found that the implementation of the iSharing application actually became a burden for Samapta members because when carrying out patrols, they were required to be online using communication tools during the patrol. This actually places a burden on Samapta because in terms of carrying out patrols there are certain conditions which allow team members not to always be online using communication tools considering that when using a tool there are of course limitations such as the connection and battery power of the team when carrying out patrols. Apart from that, factors were also found that had an influence on the implementation of Samapta patrol supervision through the iSharing application in preventing criminal acts of motorbike theft in the jurisdiction of the Kediri City Police in the form of people, money, materials and methods.